High thermoelectric performance realized through manipulating layered phonon-electron decoupling - Su, Lizhong; Wang, Dongyang; Wang, Sining; Qin, Bingchao; Wang, Yuping; Qin, Yongxin; Jin, Yang; Chang, Cheng; Zhao, Li-Dong (Science (American Association for the Advancement of Science), 2022)
Thermoelectric materials allow for direct conversion between heat and electricity, offering the potential for power generation. The average dimensionless figure of merit ZT ave determines device efficiency. N-type tin selenide crystals exhibit outstanding three-dimensional charge and two-dimensional phonon transport along the out-of-plane direction, contributing to a high maximum figure of merit Z max of ~3.6 × 10 −3 per kelvin but a moderate ZT ave of ~1.1. We found an attractive high Z max of ~4.1 × 10 −3 per kelvin at 748 kelvin and a ZT ave of ~1.7 at 300 to 773 kelvin in chlorine-doped and lead-alloyed tin selenide crystals by phonon-electron decoupling. The chlorine-induced low deformation potential improved the carrier mobility. The lead-induced mass and strain fluctuations reduced the lattice thermal conductivity. Phonon-electron decoupling plays a critical role to achieve high-performance thermoelectrics. Thermoelectic materials convert heat to electricity and are attractive for energy generation or solid-state cooling. Su et al . found that doping tin selenide with chlorine and lead substantially improved the thermoelectric figure of merit over a wide temperature range. This effect was mostly due to an improvement in the material’s deformation potential related to mass and strain fluctuations introduced into the n-type material. Improving the figure of merit in this way is challenging because properties are often intertwined and trying to improve one will often degrade others. —BG Doping tin selenide with lead and chlorine results in a material with high thermoelectric efficiency over a broad temperature range.